2016
DOI: 10.1002/adem.201600270
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Forging Cracks during Hot Compression of Powder Metallurgy Nickel‐Based Superalloy on Simulation and Experiment

Abstract: Hot compression tests on a newly designed hot extrusion Nickel-based powder metallurgy superalloy are conducted at various deformation conditions. The contact friction coefficient (f) between the die and forged part is determined as 0.30-0.40 by analyzing the results of simulation and the real experiment. A new coefficient B is introduced to evaluate the bulging levels and relate the value of f. The critical strains to prevent peripheral cracks are found to relate closely to the processing parameters. Thermall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 19 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…However, lower strain rate results in more failure than a higher strain rate at 1050 C when −𝜀 𝑇 = 0.41. These observations are in line with the study of He et al [7], where it was reported that there existed a critical strain for the onset of failure and a lower strain rate caused the earlier failure. The result is also consistent with Zhang et al's study [9],…”
Section: Fea Simulated Hot Compressionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, lower strain rate results in more failure than a higher strain rate at 1050 C when −𝜀 𝑇 = 0.41. These observations are in line with the study of He et al [7], where it was reported that there existed a critical strain for the onset of failure and a lower strain rate caused the earlier failure. The result is also consistent with Zhang et al's study [9],…”
Section: Fea Simulated Hot Compressionsupporting
confidence: 93%
“…These defects will most likely induce deformation cracks in the P/M superalloy when reaching a threshold strain, leading to a narrow processing window. He et al [7] studied the forging cracks of a P/M Ni-based superalloy in the state of HEX condition, and found the existence of TIP and MC type carbides at grain boundaries accounted for the failure initiation through examining the microstructure evolution at different strains. They also employed dichotomy theory to determine the critical failure strains under different TMP conditions and found that the failure strain increased with the increase of temperature and/or strain rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, PPB are difficult to be broken and eliminated at low temperature, which facilitates the crack nucleation and propagation during thermal consolidation [17]. The microcrack along the PPB are mainly caused by local stress concentration [18,19]. With the increase of consolidation temperature, the thermal activation of the material increases, the atomic diffusion rate accelerates, and the kinetic energy of the atoms increases, weakening the binding force between atoms, the softening effect of the material becomes obvious.…”
Section: Macroscopic Cracking Analysismentioning
confidence: 99%
“…6 Moreover, their thermal plasticity was relatively poor at high temperature and therefore made them hard to be severely deformed. 5,7 Hence, defects such as cracks and flow instabilities were easy to occur during hot processing 8,9 and the processing window of the Ni-based P/M superalloys might be comparatively narrow. 10 That might be the reason why improving processing methods of the Ni-based P/M superalloys is of great importance and worthy of a thorough investigation now.…”
Section: Introductionmentioning
confidence: 99%